2015
DOI: 10.3109/08039488.2015.1056752
|View full text |Cite
|
Sign up to set email alerts
|

Decreased dehydroepiandrosterone sulphate levels in adolescents with post-traumatic stress disorder after single sexual trauma

Abstract: Decreased DHEA-S levels and correlation with depressive symptoms are evidence for a dysregulated HPA-axis in female adolescent single sexual trauma victims with PTSD. Further research is now recommended with large patient groups in order to maximize generalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…These studies investigated CM in PTSD patients with mixed results: whereas one study observed an association of CM with elevated concentrations of DHEA in blood plasma of PTSD patients [24], another study investigating a sample of adult smokers with and without PTSD did not find a significant effect of CM on DHEA concentrations in blood serum [18]. In the aftermath of sexual trauma, PTSD patients showed significantly reduced DHEA levels compared to age-matched controls in two studies measuring steroids in saliva [25] and blood [26]. As all reported studies investigated DHEA in blood, the assessment of DHEA in hair as a cumulative measure over time might clarify the existing inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%
“…These studies investigated CM in PTSD patients with mixed results: whereas one study observed an association of CM with elevated concentrations of DHEA in blood plasma of PTSD patients [24], another study investigating a sample of adult smokers with and without PTSD did not find a significant effect of CM on DHEA concentrations in blood serum [18]. In the aftermath of sexual trauma, PTSD patients showed significantly reduced DHEA levels compared to age-matched controls in two studies measuring steroids in saliva [25] and blood [26]. As all reported studies investigated DHEA in blood, the assessment of DHEA in hair as a cumulative measure over time might clarify the existing inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, and relevant to the current discussion, the authors concluded that DHEA failed as trauma indicator, as it was found to be significantly influenced by personality. In terms of adolescent PTSD, both acute (single event rape) and chronic (repeated sexual abuse) trauma was reported to be associated with decreased DHEA concentrations [58,59]. Current data similarly indicates DHEAs levels below the expected normal range for the majority of study participants with high anxiety proneness in the absence of trauma exposure.…”
Section: Discussionmentioning
confidence: 61%
“…[5] DHEA-S could not differentiate between primary or secondary adrenal failure and low DHEA-S also found after post-traumatic stress disorder and depressive symptoms. [21] The worst performance was plasma ACTH in this study. This result proved before, where it is useful in the diagnosis of primary AI.…”
Section: Discussionmentioning
confidence: 99%
“…[5] The potential application of this study is that DHEA-S used as a tool to diagnose hypothalamic pituitary adrenal dysfunction in the afternoon because DHEA-S not subjected to circadian rhythm due to prolonged half-life. [11,20,21,[26][27][28] Since the majority of HPAD will present at afternoon to the emergency units or hospitals were the short cosyntropin not feasible and serum cortisol, and plasma ACTH will become unreliable.…”
Section: Discussionmentioning
confidence: 99%